(untitled) (Research, Society and Development, 2021)
Objective: to identify the presence of Burnout Syndrome in university professors in the context of health, work and illness relationships. Methods: descriptive cross-sectional study, in which the JBEILI questionnaire was used, developed and adapted by Chafic Jbeili, inspired by the Maslach Burnout Inventory, adapted and validated, using the Websurveys strategy from a form implemented in the Google Forms platform. Sample constituted by 108 professors, distributed among 11 Departments. The Kruskal-Wallis comparative test, the Levene test, the Shapiro-Wilk test and the multiple comparisons test were applied. Results: 108 professors from a public higher education institution participated in the study, 88.8% women and 11.2% men, distributed in 11 departments, three of which had a high rate of signs for the syndrome in the initial phase. Conclusion: it was identified that professionals from the Departments of Nursing, Dentistry and Occupational Therapy are in the initial stage of Burnout Syndrome.